PERLINDUNGAN HUKUM HAK PENCIPTA LAGU MELALUI PERAN LEMBAGA MANAJEMEN KOLEKTIF NASIONAL (LMKN) BERDASARKAN PP NO. 56 TAHUN 2021 - Karel Martinus Siahaya; Dyah Permata B A (Universitas Janabadra, 2022)
Abstract: The authority to withdraw, collect and distribute royalties from the Collective Management Institute and the National Collective Management Institute has a long tail, considering that the LMK in Indonesia itself (Multi LMK). The government ratified Government Regulation Number 56 of 2021 concerning Management of Song Copyright Royalties on March 30, 2021 in order to achieve efficiency in the collection, collection and distribution of royalties. The purpose of this study was to analyze and find out how the role of the National Collective Management Institute in optimizing the management of royalties for the use of creations and related rights products in the field of songs and music. The research method used is qualitative with the type of descriptive research, with the type of empirical juridical research with a focus on examining the rules or norms in the applicable positive law. In collecting data, this study used an observation and interview approach by going through the stages of data reduction, data presentation and drawing conclusions.